Analisis Framing Pemberitaan Kasus Kekerasan Pada Diksar Unit Kegiatan Mahasiswa Kampus Litbang UIN Raden Fatah Palembang - Miranthi Sandana; Eni Murdiati; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This research is entitled " Framing Analysis of Reporting on Violence Cases in the Litbang Diksar Student Activity Unit at UIN Raden Fatah Palembang". In the current era of globalization, understanding information greatly influences the progress of a country, including the mindset of the people living in it. The formation of people's mindset in a country is greatly influenced by the information they have obtained. The information obtained can be easily absorbed by the public if assisted by supporting media for the process of disseminating the information. This information can be disseminated to all corners of the country through the media used, both print and electronic media. The very easy and fast distribution and delivery of information makes some news media forget their purpose. A lot of dishonest news, news that leads public opinion to cause riots is spread on online media and has a negative impact on the victims themselves. Thus, framing is needed in news to see how the media frames or constructs reality, atmosphere, circumstances, and even opinions related to the event. The method used in this research is a qualitative approach, which focuses on observing the reality that occurs in order to confirm the research. The process of finding answers to a problem, how social events can be shaped so that they have meaning. The purpose of this research is to determine the media Sumeks.co and Sripoku.com in framing reporting on cases of violence in the Litbang Diksar Student Activity Unit at UIN Raden Fatah Palembang. Based on the results of the analysis of how the Sumeks.co and Sripoku.com media framed reporting on cases of violance, based on Robert N. Entman's four framing concepts, namely defining the problem, diagnosing the cause or source of the problem, making a moral judgment or taking moral decisions, and recommendations for treatment or problem solving, it is concluded that there are differences in framing in the two online media. Sumeks.co media is more critical and coherent in reporting the case, does not create a bad opinion among the public about the institution involved, the problem is clear and there is no bias between the victim and the perpetrator without cornering any of the organizations involved. Meanwhile, Media Sripoku.com created an opinion explaining that violent crime is a crime that must be dealt with firmly by the authorities. The content of the news is more biased towards the institution supported by the victim, rather than the causes and factors that occurred, making it seem unbalanced and one-sided and leading public opinion to think negatively about the organization involved.